Advancements in Diplomatic Efforts of Indonesia in Combating Covid-19 Compared to ASEAN Countries in Achieving National Pandemic Resilience - Agung Tri Putra (Jurnal Mengkaji Indonesia, 2023)
Abstract: Indonesia's Diplomatic Resilience is an interesting subject to discuss, in this study the authors attempted to conduct a comparative study between Indonesia's national resilience compared to countries in ASEAN. The author takes 3 samples of countries through countries in ASEAN, namely countries with the highest GDP in ASEAN, middle, and low. This disaggregation of GDP per capita will have an impact on economic and military data which will be combined to become an important variable in the influence of Indonesian Diplomacy in realizing National Defense. The author tries to describe how Indonesia's diplomacy works to achieve national resilience, an example is how Indonesia can become a country among the G20, whereas if you look at the poverty in Indonesia, it is not as low as countries like Singapore or Malaysia. The theory that will be used in this research is the rational choice theory to explain the tendency of interaction between one country and another. In particular, the concept of rational choice theory will depart from economic, geopolitical, and military capital as well as the position of the state in the region to determine the strategic policy of a state. Purpose: The purpose of this research is to provide novelty to the study of National Resilience which rarely influences diplomacy in realizing Indonesia's national resilience. Design/Methodology/Approach: This research will use a literature study approach which will also be explored through case studies and comparisons of key variables from countries in ASEAN in determining the influence of diplomacy. Findings: There is strong power in the formulation of foreign policy to solve a problem. The instruments to carry it out are not only military and economic power, but many other factors such as territory and bargaining position as well as diplomacy. The existence of diplomacy is very important to provide further communication of national interests which can be rationalized through the power of appeal. Therefore, Indonesia can make a lot of progress in getting through the Covid-19 pandemic, especially compared to other ASEAN countries. Of course, Indonesia only lost the power of vaccine diplomacy with Singapore, which had obtained Pfizer and Moderna first. However, when compared to other countries such as Malaysia, Vietnam, and the Philippines, Indonesia has stronger diplomatic powers. Originality/Value: This research will become a new milestone in the study of national security, especially in the sphere of diplomatic resilience which is rarely used as the main variable in national security. The research indicator that will be used by the first author is the success index of diplomatic efforts both within the military and economic frameworks. This data can be obtained from the ministry of foreign affairs or related agencies of the Indonesian government. The second indicator is the national interest of the Indonesian government or the priority of negotiation and diplomacy, especially during the Covid-19 pandemic. Third, an indicator that needs to be considered is Indonesia's bargaining power compared to other countries, including diplomatic partners in obtaining its national interests.